INTERDIFUSI EFEKTIF-FUNGSI KONSENTRASI DI DALAM PADUAN TERNER Ni-Re-X (X=Ru, Co)[Concentration-Dependent Effective Interdiffusion in Ni-Re-X (X=Ru, Co) Ternarry Alloys] - Mabruri, Efendi (Jurnal Metalurgi, 2013)
This paper is addressed to the study of interdiffusion behaviour of refractory element Re with other important elements in nickel based superalloys by assesing the concentration dependence-effective interdifusion coefficients eff i D in the ternary systems of Ni-Re-X (X= Ru, Co). The assesment results showed that the effective interdifusion coefficient for Re was smaller than that for Ru and Co in the order of effRe D<effRu D<effCo D. The concentration gradient of Re had a larger influence on eff Ru D and eff Co D than the own concentration gradient of Ru and Co, respectively. On the other hand, the effective interdifusion coefficient of Re, eff Re D was not influenced by the concentration gradient of Ru and Co in the respective system. This interdiffusion behaviour reflects that the atomic bond of Ru-Re and Co-Re is larger compared to that of Ni-Ru and Ni-Co, respectively.